Stress corrosion of Ni-based superalloys - Brooking, Laurie; Sumner, Joy; Gray, Simon; Simms, Nigel J. (Taylor & Francis, 2017)
The development of gas turbines to increase fuel efficiency is resulting in progressively higher operating temperatures in the under platform regions of the blades. These regions have traditionally been considered low risk areas. However, higher metal temperatures combined with stresses and the deposition of contaminants from the cooling air system may result in complex degradation mechanisms. Static stress corrosion testing has been conducted on C-ring specimens at a range of stresses in a hot corrosion environment. Cracks were observed in C-rings after exposure times greater than 100 h. Scanning electron microscopy (SEM) systems were used to image cracks and characterise deposits to improve understanding of the mechanism. Finite element analysis (FEA) has been used to model the stress intensity under test conditions. CMSX-4 specimens subject to static stresses combined with hot corrosion demonstrated significant material degradation (crack initiation and propagation) suggesting a combined stress corrosion mechanism resulting in cracking.
Keywords: Stress corrosion; Superalloy; C-ring; FEA